Extraction and Characterization of Fe2O3 from Red Mud PT. Indonesia Chemical Alumina West Kalimantan - Wahyinto, Indi Rizki; Aritonang, Anthoni B.; Zaharah, Titin Anita (BERKALA SAINSTEK, 2022)
Red Mud is a term used for residues or waste materials from bauxite refining. One of the main compositions of red mud is Fe2O3. This study aims to obtain the optimum extraction of Fe2O3 conditions or hematite by using APDC ligands and knowing the characteristics of Fe2O3 generated. In this study, Fe2O3 extraction begins to determine the optimum pH and ligand concentration. The results of determining the optimum conditions showed pH 1 and ligand concentration of 0.5 M. Fe2O3 characteristics can be resolve through the characterization of Fourier Transformed Infra Red (FTIR), X-ray Diffraction (XRD) and X-ray Fluorescence (XRF). The results of FTIR characterization showed the stretching vibration of Fe-O Fe2O3 phase (570.50 cm-1 and 470.20 cm-1), XRD diffractogram showed the resulting crystal shape is rhombohedralsize is 27,08 nm, while the XRF characterization results showed the mass percent Fe2O3 before extraction is 42.48% and the mass percent Fe2O3 after extraction is 72.443%.